Development of nucleic acid-based vaccines against dengue and other mosquito-borne flaviviruses: the past, present, and future - Bello, Muhammad Bashir; Alsaadi, Ahlam; Naeem, Asif; Almahboub, Sarah A.; Bosaeed, Mohammad; Aljedani, Safia S. (Frontiers in Immunology, 2025)
Due to their widespread geographic distribution and frequent outbreaks, mosquito-borne flaviviruses, such as DENV (DENV), Zika virus (ZIKV), Japanese encephalitis virus (JEV), yellow fever virus (YFV), and West Nile virus (WNV), are considered significant global public health threats and contribute to dramatic socioeconomic imbalances worldwide. The global prevalence of these viruses is largely driven by extensive international travels and ecological disruptions that create favorable conditions for the breeding of Aedes and Culex species, the mosquito vectors responsible for the spread of these pathogens. Currently, vaccines are available for only DENV, YFV, and JEV, but these face several challenges, including safety concerns, lengthy production processes, and logistical difficulties in distribution, especially in resource-limited regions, highlighting the urgent need for innovative vaccine approaches. Nucleic acid-based platforms, including DNA and mRNA vaccines, have emerged as promising alternatives due to their ability to elicit strong immune responses, facilitate rapid development, and support scalable manufacturing. This review provides a comprehensive update on the progress of DNA and mRNA vaccine development against mosquito-borne flaviviruses, detailing early efforts and current strategies that have produced candidates with remarkable protective efficacy and strong immunogenicity in preclinical models. Furthermore, we explore future directions for advancing nucleic acid vaccine candidates, which hold transformative potential for enhancing global public health.